(untitled) (Journal of Educational Sciences, 2025)
The paradigmatic metamorphosis of contemporary pedagogy is predicated upon the qualitative transmutation of learners’ sociocultural profile – the emergence of the centennial cohort, whose cognitive and communicative praxis is primordially circumscribed by the digital milieu. The precocious immersion of juveniles into the realm of electronic apparatuses engenders their predilections and modalities of information apprehension, rendering the incorporation of digital instrumentarium into the didactic process a cardinal prerequisite for augmenting their engagement and scholastic efficacy. The investigation’s telos was to scrutinize the influence of a digital pedagogical-methodological ecosystem, encompassing computer graphics with three-dimensional modeling, upon the cultivation of mensurational competencies among second-grade pupils. In a non-randomized controlled quasi-experimental inquiry, 52 scholastics participated, who were apportioned into two cohorts according to their classes: experimental (n = 27) and positive control (n = 25). The digital ecosystem encompassed two 45-minute sessions for both cohorts utilizing Paint 3D software, predicated upon cognitive interaction principles. The active control cohort studied mass measurement units, emphasizing comprehension of their transformation processes, whilst the experimental cohort pursued identical methodology but additionally executed object measurements, explicating their resolutions. To assess the implemented mode’s efficacy, a 15-minute pre- and post-assessment with illustrations for determining pertinent competencies was administered, elaborated comprehensively to ensure potential replicability by other pedagogues. The assessment comprised five scales reflecting measurement essence, standard cognizance, object measurement precision, solution explication, and lexical correspondence perception. According to ANCOVA analysis, following implementation, the experimental cohort of primary scholars evinced more precise outcomes vis-à-vis their positive control counterparts in object measurement tasks, as evidenced by substantial effect magnitude and significant intergroup post-assessment disparity. The experimental cohort’s schoolers demonstrated superior mastery of explicating and substantiating their resolutions – effect magnitude was evaluated between medium and large, with the intergroup lacuna proving statistically significant. Key words: mensuration skills, digital environment, 3D modeling, quasi-experiment, digital education, pupils, elementary school.